2007
DOI: 10.1590/s0103-50532007000800015
|View full text |Cite
|
Sign up to set email alerts
|

Cu, Fe, Mn and Zn distribution in protein fractions of Brazil-nut, cupuassu seed and coconut pulp by solid-liquid extraction and electrothermal atomic absorption spectrometry

Abstract: Neste trabalho foram determinados Cu, Fe, Mn and Zn em extratos de castanha-do-Pará (Bertholletia excelsa), semente de cupuaçu (Theobroma grandiflorum) e polpa de coco (Cocos nucifera) usando extração sólido-líquido e espectrometria de absorção atômica com atomização eletrotérmica. Foram empregadas diferentes soluções extratoras (mistura de metanol e clorofórmio 1:2 v/v, água, 0,5 mol L -1 NaCl, 70% v/v etanol e 0,5 mol L -1 NaOH) para extração de lipídios, albuminas, globulinas, prolaminas e glutelinas, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 26 publications
(55 reference statements)
1
17
0
4
Order By: Relevance
“…It is well discussed in the literature 12,13 that the extractants water, NaCl, ethanol and NaOH promoted the separation of different groups of proteins: albumins, globulins, prolamins and glutelins, respectively. 12,13 The total protein concentration obtained by the masses sum of all extracts revealed that cooking promoted a sensible decrease in the protein content, mainly in the globulins fraction, when compared to the uncooked beans. Previous investigations showed that the total protein concentration ranged from 22.57 to 24.42 g per 100 g and from 23.25 to 26.29 g per 100 g for raw and cooked beans, respectively.…”
Section: Cooking Effects On Protein Concentrationmentioning
confidence: 99%
“…It is well discussed in the literature 12,13 that the extractants water, NaCl, ethanol and NaOH promoted the separation of different groups of proteins: albumins, globulins, prolamins and glutelins, respectively. 12,13 The total protein concentration obtained by the masses sum of all extracts revealed that cooking promoted a sensible decrease in the protein content, mainly in the globulins fraction, when compared to the uncooked beans. Previous investigations showed that the total protein concentration ranged from 22.57 to 24.42 g per 100 g and from 23.25 to 26.29 g per 100 g for raw and cooked beans, respectively.…”
Section: Cooking Effects On Protein Concentrationmentioning
confidence: 99%
“…The metal contents of the digested samples were determined in an Analytikjena AG, AAS ZEEnit 60 instrument. Iron, copper, and zinc were detected at 324.8, 248.3, and 213.9 nm, respectively (30).…”
Section: S Cerevisiae Strains and Growth Conditions-mentioning
confidence: 99%
“…and Zn 2? (Naozuka and Oliveira 2007 Fig. 4 In vitro digestibility of native and recombinant proteins in SGF.…”
Section: Lipid Metal-binding Propertiesmentioning
confidence: 99%